1993
DOI: 10.1111/j.1574-6968.1993.tb06121.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of transferrin-bound iron byListeria monocytogenes

Abstract: It has been demonstrated that under iron-restricted conditions, Listeria monocytogenes can utilize iron-loaded transferrin (Tf) from a range of species as its sole source of iron for growth. Human transferrin conjugated to horseradish-peroxidase (HRP-Tf) bound directly to whole cells of L. monocytogenes. This binding was blocked by apotransferrin indicating that the receptor can bind transferrin in either the iron-bound or iron-free form. Transferrin-binding was not host specific because both bovine and equine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The hsterta strains examined failed to react with HRP-HTF (Fig la) but did react with blotmylated-HTF (Fig lb) The N menmgtttdts poslttve control reacted and the E colt negattve control failed to react in both cases (Fig 1) A similar pattern of reactlvJty with blotlnylated HTF (Fig 2a) but lack of reactivity wtth HRP-HTF (FJg 3a) for llsterla strains was also apparent by Hartford et al [7] Consequently, the reaction with blotmylated-HTF supported the findings of Hartford et al [7] of a c 126 kDa transferrm binding protein m L monocytogenes NCTC 7973, whereas the lack of reactivity with HRP-HTF contradicted such a view A possible explanation was that the apparent reaction with blotmylated-HTF was not due to lnteracuon with the transferrm molecule In order to test this possibdlty separated bacterial proteins were reacted with biotmylated human lactoferrln, and reaction was seen with a band identical to the one that reacted with blotmylated-HTF (Fig 2b) An explanation of these findings was forthcoming when we demonstrated that development of a membrane previously reacted with HRP-HTF (Fig 3a) with HRP-streptavldm alone resulted m vlsualisatlon of the same c 126 kDa protein (Fig 3b) A membrane reacted with HRP-HTF but not HRP-streptavidm remained negatwe for the hstena strains examined (not shown) demonstrating that the reactions seen m Fig 3b are not due to late development The evidence shows that this proposed transferrm binding protein, which also appeared to bind btotmylated lactoferrm, is m fact a naturally biotmylated protein that binds streptavldln The mablhty to purify a 126 kDa protein by the transferrin affinity procedure further supports the conclusion that this protein is not a transferrm-bmding protein Although these findings explain the Western blot results of Hartford and colleagues [7], which they interpreted as binding to transferrin, what Is more difficult to explain is their reported binding to HRP-HTF in whole cell dot-blots We could not demonstrate this m a repeat of their method- 4 and 6 respectwely) and m non-restricted BHI (lanes 3, 5, and 7 respectively) reacted with (a) horseradish peroxadase conjugated human transfernn and (b) the same membrane following reaction with horseradish peroxldase streptavldm Arrow head the 126 kDa L monocytogenes protein * the 78 kDa transferrm binding protein 2 of N memngmdts ology or by Western blot This is unhkely to be due to strata differences as the same NCTC 7973 stram was also examined In concluston we can find no evidence in support of the view that L monocytogenes binds dtrectly to human transferrin or that thts is mediated through a 126 kDa protein…”
Section: Results and Dtscussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The hsterta strains examined failed to react with HRP-HTF (Fig la) but did react with blotmylated-HTF (Fig lb) The N menmgtttdts poslttve control reacted and the E colt negattve control failed to react in both cases (Fig 1) A similar pattern of reactlvJty with blotlnylated HTF (Fig 2a) but lack of reactivity wtth HRP-HTF (FJg 3a) for llsterla strains was also apparent by Hartford et al [7] Consequently, the reaction with blotmylated-HTF supported the findings of Hartford et al [7] of a c 126 kDa transferrm binding protein m L monocytogenes NCTC 7973, whereas the lack of reactivity with HRP-HTF contradicted such a view A possible explanation was that the apparent reaction with blotmylated-HTF was not due to lnteracuon with the transferrm molecule In order to test this possibdlty separated bacterial proteins were reacted with biotmylated human lactoferrln, and reaction was seen with a band identical to the one that reacted with blotmylated-HTF (Fig 2b) An explanation of these findings was forthcoming when we demonstrated that development of a membrane previously reacted with HRP-HTF (Fig 3a) with HRP-streptavldm alone resulted m vlsualisatlon of the same c 126 kDa protein (Fig 3b) A membrane reacted with HRP-HTF but not HRP-streptavidm remained negatwe for the hstena strains examined (not shown) demonstrating that the reactions seen m Fig 3b are not due to late development The evidence shows that this proposed transferrm binding protein, which also appeared to bind btotmylated lactoferrm, is m fact a naturally biotmylated protein that binds streptavldln The mablhty to purify a 126 kDa protein by the transferrin affinity procedure further supports the conclusion that this protein is not a transferrm-bmding protein Although these findings explain the Western blot results of Hartford and colleagues [7], which they interpreted as binding to transferrin, what Is more difficult to explain is their reported binding to HRP-HTF in whole cell dot-blots We could not demonstrate this m a repeat of their method- 4 and 6 respectwely) and m non-restricted BHI (lanes 3, 5, and 7 respectively) reacted with (a) horseradish peroxadase conjugated human transfernn and (b) the same membrane following reaction with horseradish peroxldase streptavldm Arrow head the 126 kDa L monocytogenes protein * the 78 kDa transferrm binding protein 2 of N memngmdts ology or by Western blot This is unhkely to be due to strata differences as the same NCTC 7973 stram was also examined In concluston we can find no evidence in support of the view that L monocytogenes binds dtrectly to human transferrin or that thts is mediated through a 126 kDa protein…”
Section: Results and Dtscussionsupporting
confidence: 62%
“…The strams of L monocytogenes used were NCTC 7973 (serotype la), which was the strain used by Hartford et al [7], NCTC 11994 (serotype 4b) both from the National Collection of Type Cultures (Cohndale, UK), and IA486C (serotype 4b, a gift from Dr B Wren, St Bartholomews Hospital, London, UK) A laboratory faecal ~solate of Eschenchta cob 0157 H7 was used as a negative control and N menmgmdts strain SD (B15 P1 16) described previously [11] as a positwe control All strains were cultured on Columbia horse blood agar or grown in brain-heart-infusion broth (BHI, Merck) at 37°C aerobically m 5% CO 2 Iron hmltatlon for cultures of L monocytogenes and E colt was achieved as described by Hartford et al [7] by addition of ethylenediamme dl-o-hydroxyphenylacetate (EDDHA, Sigma), treated by the method of Rogers [12], to a final concentration of 100 tzM Cultures were grown at 37°C with shaking in 15 ml of culture medium to late log phase Cells were then harvested by centrlfugation at 1200 × g at 4°C for 30 mm, and the resultant pellets washed once with phosphate buffered sahne (PBS), re-pelleted, and re-sus-pended in 500/xl of 10 mM Trls-HCL (pH 7 4) to concentrate Protein est~mation of each bacterml culture was performed by the method of Bradford [13] using the Pierce protein estimation kit (Pierce) N menmgtttdzs was grown under ~ron-hmitatlon by previously described methods [11] Transferrm and lactoferrm bmdmg assays Three methods were used to detect transferrm binding proteins, whole cell dot lmmuno-blots, Western blots, and transferrm affimty purification For whole-cell dot lmmuno-blots 15 /zl (1 /zg/ml) of bacterial cells harvested following growth under iron-sufficient or iron-restricted conditions were spotted onto nitrocellulose membrane (Schlelcher and Schuell), the membrane blocked with 3% blocking buffer (consisting of 3% w/v skimmed milk and 0 1% Tween 20 m PBS), and probed with either 1 /zg/ml horseradish peroxadase conjugated human transferrm (HRP-HTF, Stratech Scientific Ltd), or 1 mg/ml biotin conjugated human transferrin (B-HTF), or 1 mg/ml biotin conjugated human lactoferrm (B-HL) B-HTF and B-HL were prepared according to the method described by Schryvers [11] Development was with 4-chloro-1-napthol (Sigma) for HRP-HTF reactions and HRP-streptavldm (50 ng/ml) (Jackson Immuno Research Lab Inc,) followed by 4-chloro-lnapthol for B-HTF and B-HL reactions These experiments were repeated using 3% (w/v) gelatin as the blocking agent For Western blots 50 /~g of bacterial protein were somcated at 12 × 103 m~crons for 5 mm (MSE somprep 150), dissolved in SDS and boiled and separated by sodium dodecyl sulphate 10% polyacrylamlde gel electrophoresls (SDS-PAGE) and transferred to nitrocellulose as described m detail elsewhere [11] The membranes were blocked with blockang buffer containing milk, then probed and developed as described above for whole-cell dot blots In addition the membrane which was reacted with HRP-HTF and developed was re-probed with HRP-streptavldm without prior incubation with a blotmylated compound An ldentxcal membrane to the one that was reprobed was incubated m parallel without re-prob-mg to confirm that any positive reaction seen following this procedure was not due simply to a late developing reaction of the HRP-HTF…”
Section: Bacterial Strams and Growth Condmonsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The acquisition of iron from host proteins has been studied in just a handful of Gram-positive microbes. Some species employ surface receptors for proteins, such as transferrin or lactoferrin, 11,12 while other Gram-positive bacteria, for example Bacillus subtilis, utilize siderophores to obtain ferric iron. 13 The use of haem or heamo proteins mediated through dedicated surface receptors has also been reported.…”
Section: Introductionmentioning
confidence: 99%